2012
DOI: 10.1111/j.1464-410x.2012.11279.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term oncological and continence outcomes after laparoscopic radical prostatectomy: a single‐centre experience

Abstract: E 9 8 5What ' s known on the subject? and What does the study add? Over the past decade, minimally invasive laparoscopic radical prostatectomy and more recently robot-assisted laparoscopic prostatectomy have been introduced and have proven equally effective compared with open surgery in terms of mid-term cancer control and complication rates. Because long-term data is lacking, open prostatectomy is still considered the ' gold standard ' by some authors, who argue that minimally invasive approaches have to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
3
19
1
4
Order By: Relevance
“…In our study, the 5-year PSA failure-free rate was 70.5%, and the prognostic factors for PSA failure were resection margin, EPE, and tumor diameter. The 5-year PSA failure-free survival for patients with a negative resection margin was 81.6%, and these results were similar to that in other reports [7][8][9][10]13].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In our study, the 5-year PSA failure-free rate was 70.5%, and the prognostic factors for PSA failure were resection margin, EPE, and tumor diameter. The 5-year PSA failure-free survival for patients with a negative resection margin was 81.6%, and these results were similar to that in other reports [7][8][9][10]13].…”
Section: Discussionsupporting
confidence: 81%
“…Sooriakumaran et al reported that among 22,393 cases, the PRM of LRP was 16.3%, and that it was better than that of RRP, but was worse than that of RARP [14]. Other reports, including many LRP cases, concluded that the PRM varied from 7.4% to 29.2% [7][8][9][10]. Yossepowitch et al reported that a PRM increased the PSA failure rate 1.6-5.0-fold [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations